Sequência didática anti-homofobia: discutindo homossexualidades no ensino de história do terceiro ano médio do Colégio Estadual Reis Magalhães em Glória-BA - Sá Júnior, Cláudio Gomes de (2023)
I It is understood today that people Lesbian, Gay, Bisexual, Transvestite, Transsexual, Queer, Intersex, Asexual and all other sexual and gender identities (LGBTQIA+) have had, in the context of Western Christian history, their identities and humanities denied, silenced , monitored and/or punished by a set of power mechanisms created and reproduced by institutions, such as the Catholic apostolic church, medicine, the family and historiography itself. This oppressive logic structurally affected social relationships and mentalities that, consequently, affect the State and its apparatus, including the School. In the 20th century, Brazilian schools included sexual education in their curricula, however, it consists of a hygienist sexual education that treats sexualities only from a biological perspective, omitting identities and producing inequalities. In the current century, the State recognizes the existence of homophobia in schools and creates public policies for the continued training of education professionals, which was of paramount importance. However, this measure is still insufficient for the demands of this social group, so it opens up the prerogative for undergraduate researchers to associate their studies with teaching practices. From this, curricular documents include, as a school objective, training for citizenship and respect for human pluralities. From this perspective, this research understands that History teaching and teachers have great potential in transforming realities, although there are obstacles that hinder the transdisciplinary work of this science with the theme of homosexuality, whether due to lack of training and/or for not having access to pedagogical tools that make this link. Thus, through this assumption, this dissertation presents a didactic sequence that discusses homosexuality in the teaching of History in the third year of high school at Colégio Estadual Reis Magalhães, in the city of Glória-BA, and which can be used as a reference for professionals who aspire to such debate